2020
DOI: 10.1161/jaha.119.017625
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictive Models of Sudden Cardiac Arrest: A Survey of the Current Science and Analysis of Model Performances

Abstract: Background More than 500 000 sudden cardiac arrests (SCAs) occur annually in the United States. Clinical predictive models (CPMs) may be helpful tools to differentiate between patients who are likely to survive or have good neurologic recovery and those who are not. However, which CPMs are most reliable for discriminating between outcomes in SCA is not known. Methods and Results We performed a systematic review of the literature using the Tufts PACE (Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 126 publications
0
41
0
Order By: Relevance
“…Several studies have reported models for predicting the outcomes of CA patients [ 8 ]. In a systematic review of current prediction models, the median AUROC value was 0.84 with an IQR of 0.80 to 0.89 [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported models for predicting the outcomes of CA patients [ 8 ]. In a systematic review of current prediction models, the median AUROC value was 0.84 with an IQR of 0.80 to 0.89 [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic factors and prediction tools for survivors of IHCA and their neurologic outcomes have been identified in previous studies [ 3 - 8 ]. However, the evidence of an early warning system for predicting the mortality of IHCA survivors is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Bisbal et al reported the SAPS III as less accurate in determining the in-hospital mortality of post-CA patients compared to other general prognostic scores 39 . Signi cant efforts have been made in recent years to develop scoring systems that can be used to estimate the outcome of resuscitated patients 40 , and these often require background information about the patient and about often missing peri-arrest circumstances. Though promising, these scores are not as widely used as the classic general prognostic scores.…”
Section: Discussionmentioning
confidence: 99%
“…These include old age, unwitnessed cardiac arrest, lack of bystander CPR, achievement of return of spontaneous circulation (ROSC) after 30 min of CPR, initial non-shockable rhythm, elevated lactate level, and low pH (< 7.2) [ 13 •]. The 3 most commonly used predictors of outcome are initial cardiac rhythm, age, and CPR duration [ 14 ]. Some of the predictive models used in clinical practice are discussed below.…”
Section: Assessment and Risk Stratificationmentioning
confidence: 99%